2002
DOI: 10.1046/j.1365-8711.2002.05236.x
|View full text |Cite
|
Sign up to set email alerts
|

On the black hole-bulge mass relation in active and inactive galaxies

Abstract: New black hole mass estimates are presented for a sample of 72 active galactic nuclei (AGNs) covering three decades in optical luminosity. Using a subsample of Seyfert galaxies, which have black hole mass estimates from both reverberation mapping and stellar velocity dispersions, we investigate the geometry of the AGNs’ broad‐line region. It is demonstrated that a model in which the orbits of the line‐emitting material have a flattened geometry is favoured over randomly‐orientated orbits. Using this model we i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

75
595
7
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 521 publications
(680 citation statements)
references
References 45 publications
75
595
7
1
Order By: Relevance
“…In Figure 10 we report the relationship between M(BH) and host galaxy absolute magnitude Mi compared with the local relation by Bettoni et al (2003) that is in good agreement with those by McLure & Dunlop (2002) and Ferrarese (2002) based on similar datasets. The local relation by (Bettoni et al 2003) that is calibrated on the R (Vega mag system) filter was transformed into Mi taking into account both the different cosmology assumed and the filter transformations.…”
Section: Comparison With Previous Studiessupporting
confidence: 67%
“…In Figure 10 we report the relationship between M(BH) and host galaxy absolute magnitude Mi compared with the local relation by Bettoni et al (2003) that is in good agreement with those by McLure & Dunlop (2002) and Ferrarese (2002) based on similar datasets. The local relation by (Bettoni et al 2003) that is calibrated on the R (Vega mag system) filter was transformed into Mi taking into account both the different cosmology assumed and the filter transformations.…”
Section: Comparison With Previous Studiessupporting
confidence: 67%
“…Firstly, Magorrian et al (1998) found that the kinematic data of 36 nearby galaxies indicate the presence of a massive dark object in the center of the galaxies and that the mass of the dark object correlates with the bulge luminosity and mass. Recent studies of this relationship obtain M BH ∼ 0.001M bulge (McLure & Dunlop 2002;Merritt & Ferrarese 2001). Secondly, the central velocity dispersion of the bulge σ 0 has been found to exhibit a tight correlation with the central black hole mass (Ferrarese & Merritt 2000, Gebhardt et al 2000.…”
Section: Introductionmentioning
confidence: 87%
“…Two M BH measurements were found for this blazar. The value of log(M BH /M ) = 8.69, given by Falomo et al (2003a), is based on the correlation with the host galaxy bulge luminosity in R-band (M R − M BH , McLure & Dunlop (2002)). Based on the same galaxy property correlation M R − M BH , a value of log(M BH /M ) = 8.5 was reported by Wu et al (2009).…”
Section: Smbh Masses and Corresponding Time Scalesmentioning
confidence: 99%